Comparative study of LPBF Ta–Ti alloy: microstructural evolution and deformation behavior - Zhenyu Yang; Yuanhong Qiu; Jiangqi Zhu; Zhifeng Huang; Shengbin Dai; Weihu Yang; Min Liu; Gang Wang; Xingchen Yan; Wenhua Huang (Journal of Materials Research and Technology)
Tantalum faces limitations in bone implant applications due to stress shielding induced by high elastic modulus, along with processing challenges for Ta-based alloys. In this study, we fabricated in-situ alloyed Ta–Ti samples via laser powder bed fusion technology, systematically investigating the role of Ti elements in microstructural modification and mechanical strengthening. The quasi-in-situ electron backscatter diffraction technique was innovatively combined with molecular dynamics simulations to dynamicly track the deformation mechanisms and resolve multiscale interactions. Results demonstrate that Ti addition promotes columnar-to-equiaxed transition through constitutional undercooling, while unmelted Ta particles act as heterogeneous nucleation sites. This dual mechanism refined grain size by 89 % (from 164.5 μm in pure Ta to 18.0 μm). During small deformations, refined grains facilitated uniform strain distribution; however, unmelted particles triggered stress concentration at high strains, reducing fracture elongation to 20 % and inducing mixed ductile-brittle fracture. Optimal parameters (laser power 240 W, scanning speed 660 mm/s) achieved a Vickers hardness of 297.2 HV. This work pioneers the correlation of quasi-in-situ observed strain partitioning with simulated solidification pathways, providing foundational insights for high-strength biomedical Ta alloy design.